Input/Output Devices and Interaction Techniques (2007) - Hinckley, Ken; Jacob, Robert J. K.; Ware, Colin; Wobbrock, Jacob O.; Wigdor, Daniel (Computing Handbook, Third Edition, 2014)
The computing literature often draws a sharp distinction between input and output; computer scientists are used to regarding a screen as a passive output device and a mouse as a pure input device. However, nearly all examples of human-computer interaction require both input and output to do anything useful. For example, what good would a mouse be without the corresponding feedback embodied by the cursor on the screen, as well as the sound and feel of the buttons when they are clicked? The distinction between output devices and input devices becomes even more blurred in the real world. A sheet of paper can be used to both record ideas (input) and display them (output). Clay reacts to the sculptor’s fingers yet also provides feedback through the curvature and texture of its surface. Indeed, the complete and seamless integration of input and output is becoming a common research theme in advanced computer interfaces such as ubiquitous computing (Weiser, 1991) and tangible interaction (Ishii & Ullmer, 1997). Further, as the space required for a powerful computer has plummeted, new form factors have emerged. In mobile devices, the desire to provide large screens to maximize media consumption experiences has marginalized dedicated control surfaces, replacing physical keyboards and pointing devices with ad hoc screen-rendered controls manipulated through touch input. Although measurably inferior at nearly all input tasks, touchscreens have none the less emerged as a dominant form of mobile computing.